Cuando los lugares dirimidos hablan: precariedad en la obra de Carmen Berenguer, Gabriela Cabezón Cámara, Diamela Eltit y Samanta Schweblin (Dossier: Producir presente: tocar el cuerpo, escritura, mujeres, paisajes, afectos. Narrativa contemporánea de escritoras en América Latina, II) - Sotomayor Miletti, Áurea María (2020)
The article reflects on a narrative corpus borne out of the Southern Cone from a viewpoint that articulates places, speech, community, response, and documentation. The texts that constitute the corpus of “documentary fiction”, that are the object of this study, are Naciste pintada (1999), by Carmen Berenguer; a segment of a judicial file, Puño y letra (2005), by Diamela Eltit; a political action turned into a local art performance that is exported to Venice, El romance de la negra rubia (2014), by Gabriela Cabezón Cámara and a contaminated territory inhabited by the agonizing delirium of the narrator, Distancia de rescate (2014), by Samanta Schweblin. The studied narratives propose another model in which, although violence is documented, it is recorded in a different way, and questions concerning violent becomings are centered on the speeches that distribute them, emphasizing the range of speech itself which remains open.